Tumor Microenvironment Immune Response in Pancreatic Ductal Adenocarcinoma Patients Treated With Neoadjuvant Therapy. (4th June 2020) - Michelakos, Theodoros; Cai, Lei; Villani, Vincenzo; Sabbatino, Francesco; Kontos, Filippos; Fernández-del Castillo, Carlos; Yamada, Teppei; Neyaz, Azfar; Taylor, Martin S; Deshpande, Vikram; Kurokawa, Tomohiro; Ting, David T; et al.
Abstract: Background: Neoadjuvant folinic acid, fluorouracil, irinotecan, and oxaliplatin (FOLFIRINOX) and chemoradiation have been used to downstage borderline and locally advanced pancreatic ductal adenocarcinoma (PDAC). Whether neoadjuvant therapy-induced tumor immune response contributes to the improved survival is unknown. Therefore, we evaluated whether neoadjuvant therapy induces an immune response towards PDAC. Methods: Clinicopathological variables were collected for surgically resected PDACs at the Massachusetts General Hospital (1998-2016). Neoadjuvant regimens included FOLFIRINOX with or without chemoradiation, proton chemoradiation (25 Gy), photon chemoradiation (50.4 Gy), or no neoadjuvant therapy. Human leukocyte antigen (HLA) class I and II expression and immune cell infiltration (CD4 +, FoxP3 +, CD8 +, granzyme B + cells, and M2 macrophages) were analyzed immunohistochemically and correlated with clinicopathologic variables. The antitumor immune response was compared among neoadjuvant therapy regimens. All statistical tests were 2-sided. Results: Two hundred forty-eight PDAC patients were included. The median age was 64 years and 50.0% were female. HLA-A defects were less frequent in the FOLFIRINOX cohort ( P = .006). HLA class II expression was lowest in photon and highest in proton patients ( P = .02). The FOLFIRINOX cohort exhibited the densest CD8 + cell infiltration ( P < .001). FOLFIRINOX and proton patients had the highest CD4 + and lowest T regulatory (FoxP3 + ) cell density, respectively. M2 macrophage density was statistically significantly higher in the treatment-naïve group ( P < .001) in which dense M2 macrophage infiltration was an independent predictor of poor overall survival. Conclusions: Neoadjuvant FOLFIRINOX with or without chemoradiation may induce immunologically relevant changes in the tumor microenvironment. It may reduce HLA-A defects, increase CD8 + cell density, and decrease T regulatory cell and M2 macrophage density. Therefore, neoadjuvant FOLFIRINOX therapy may benefit from combinations with checkpoint inhibitors, which can enhance patients' antitumor immune response.